Inter‐specific differences in invader and native fish functional responses illustrate neutral effects on prey but superior invader competitive ability. (15th July 2019) - Mofu, Lubabalo; South, Josie; Wasserman, Ryan J.; Dalu, Tatenda; Woodford, Darragh J.; Dick, Jaimie T. A.; Weyl, Olaf L. F.
Abstract: Inter‐specific interactions are key factors in the structuring and functioning of ecological communities. Therefore, it is necessary to assess species interactions, such as predator–prey dynamics and competitive exclusion, within the context of continuing global species introductions. The aim of the present study was to assess ecological impacts and competitive exclusion dynamics involving co‐occurring introduced and native fish species, using the multiple predator functional response (FR) approach. We use comparative FR analysis (resource uptake as a function of resource density) to assess inter‐specific interactions between the invasive western mosquitofish Gambusia affinis and the native freshwater river goby Glossogobius callidus towards chironomid larvae. The FR was derived for each fish species as individuals and when in heterospecific pairings. Data from single individuals were used to predict the expected FR of individuals when in heterospecific multiple predator combinations. Expected FRs were then compared to the observed FRs of each predator in combination trials, enumerated using prey items in their gut contents. Both fish species displayed Type II FRs, however, in single fish trials, invasive mosquitofish had significantly higher FRs (curve asymptotes; i.e. shorter handling times and higher maximum feeding rates) than native river gobies. Heterospecific mosquitofish‐river goby combinations revealed that the FR of the river goby was reduced (i.e. longer handling times and lower maximum feeding rates) by the presence of mosquitofish, whereas this combination greatly enhanced mosquitofish FR magnitudes (i.e. shorter handling times and higher maximum feeding rates). The heterospecific treatments resulted in neutral impacts on prey and there were clear inter‐species interference in favour of the non‐native mosquitofish. This study demonstrates how multiple predators can alter the shape of individual FRs, with neutral effects on prey but superior invader competitive ability. This has implications for predicting the naturalisation success of invasive predators, as predatory and competitive interactions with native predators and prey may facilitate rather than impede establishment.